The effects of local and landscape context on leafhopper (Hemiptera: cicadellinae) communities in coffeee agroforestry systeMON of Costa Rica - Ramos, M. (CATIE, Turrialba (Costa Rica) University of Idaho, Moscow, ID (EUA), 2014)
Tesis (Ph. D) -- CATIE, Turrialba (Costa Rica), 2008